FAKTOR-FAKTOR YANG MEMPENGARUHI KONSERVATISME AKUNTANSI DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI PADA PERUSAHAAN PEFINDO25 - Tegar Dwi Pamungkas; Gustinya, Diana (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This research was conducted to examine the influence of Financial Distress, Litigation Risk, Company Size on Accounting Conservatism in Indonesian Pefindo25 companies listed on the Indonesia Stock Exchange from 2016 to 2021. The research sample used was 25 Pefindo25 companies. The sampling technique used was purposive sampling. The analysis method used is Moderated Regression Analysis (MRA). Based on the results of the t test, it shows that Financial Distress, Litigation Risk has an effect on Accounting Conservatism and. Company size can moderate the influence of financial distress on accounting conservatism. Company size can moderate the influence of litigation risk on accounting conservatism. At the Pefindo25 company on the Indonesian Stock Exchange